PSSE: Parenting Style Sex Education, on Understanding Sexual Violence What Parents Do Towards Children in Tiktok - Fitri, Azalia Cahya Gita; Putri, Dhea Anggraeni; Desyasti, Falaah Azurra; Humaira, Lenggogeni Trity; Syakuuron, Muhammad Abdan; Yohana, Nining Ni'mah; Briana, Regina Fajari (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
Child sexual abuse is the involvement of children in all forms of sexual activity that occurs before the child reaches the age limit set by state law and is carried out by adults or older people for sexual pleasure. Based on data from the Online Information System for the Protection of Women and Children in 2023, the highest number of cases of violence based on the place of occurrence occurred in the household sphere, which amounted to 15,450 cases with the most experienced type of violence being sexual violence at 11,191 cases. The purpose of this study is to provide information and education about "Sexual Violence According to the Aspects of Parents" so that people, especially parents, can find out about sexual violence and will not do this to their children. The method used is the literature review method by collecting various articles that have discussed sexual violence according to the views of parents and quantitative methods in calculating research results. The results of the study obtained that our educational video aired for a week received a total audience of 1,171 views with 24 likes, 1 comment, 8 shares and 6 accounts saved the video. 52% of the video viewers were female and 56% were in the age range of 25-34 years. With the results of the audience mentioned above, which is mostly adults, it is hoped that it can increase their insight and empathy to be more concerned about preventing sexual violence against children.